Digital Crisis Communication and Organisational Resilience in Nigeria: Analysis of Stakeholder Engagement and Reputation Recovery - Abdullahi Aliyu Maiwada; Okuchemiya Success; Kayode Oluwafemi Ishola (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2026)
This paper examines digital crisis communication and organisational resilience in Nigeria, with particular attention to stakeholder engagement and reputation recovery. The rapid expansion of social media and digital communication platforms has transformed crisis management by increasing the speed, visibility, and interactivity of organisational crises. Using secondary data obtained from existing scholarly literature, published research, books, institutional reports, and documented cases of organisational crisis communication, the study critically analyses how Nigerian organisations respond to crises in digitally mediated environments. Guided by Situational Crisis Communication Theory (SCCT), the study explores the relationship between crisis response strategies, stakeholder engagement, organisational reputation, and resilience. The analysis indicates that effective digital crisis communication is characterised by timeliness, transparency, accountability, empathy, consistency, and continuous stakeholder engagement. It further demonstrates that organisations that actively monitor digital conversations, provide accurate and timely information, acknowledge stakeholder concerns, and adopt response strategies that correspond with perceived crisis responsibility are better positioned to minimise reputational damage and recover stakeholder trust. Conversely, delayed responses, defensive communication, inconsistent messaging, and inadequate engagement may intensify misinformation, public backlash, and reputational decline. The study concludes that digital crisis communication should be integrated into organisational resilience frameworks and strategic public relations planning in Nigeria. It recommends the development of proactive digital crisis protocols, investment in digital listening and analytics capabilities, continuous stakeholder engagement, ethical and transparent communication, and post-crisis learning mechanisms to strengthen organisational resilience and support sustainable reputation recovery.